2020
DOI: 10.1002/cpt.1966
|View full text |Cite
|
Sign up to set email alerts
|

An Electronic Health Record Text Mining Tool to Collect Real‐World Drug Treatment Outcomes: A Validation Study in Patients With Metastatic Renal Cell Carcinoma

Abstract: Real‐world evidence can close the inferential gap between marketing authorization studies and clinical practice. However, the current standard for real‐world data extraction from electronic health records (EHRs) for treatment evaluation is manual review (MR), which is time‐consuming and laborious. Clinical Data Collector (CDC) is a novel natural language processing and text mining software tool for both structured and unstructured EHR data and only shows relevant EHR sections improving efficiency. We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
1
16
1
Order By: Relevance
“…Baseline characteristics, medication use, comorbidities, and outcomes were extracted from the Electronic Health Records, by a Natural language processing and text mining-based tool validated in previous study. 16 For details see methods in the Data Supplement .…”
Section: Methodsmentioning
confidence: 99%
“…Baseline characteristics, medication use, comorbidities, and outcomes were extracted from the Electronic Health Records, by a Natural language processing and text mining-based tool validated in previous study. 16 For details see methods in the Data Supplement .…”
Section: Methodsmentioning
confidence: 99%
“…Also, it is possible that we underestimated the number of patients with myalgia and its severity, because the medical records were initially screened using the CDC. However, a recent study has shown that the use of this search engine is reliable and accurate 27 . Overestimation is highly unlikely, because all EHRs with a positive hit were screened and confirmed manually.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of an electronic health record text mining tool has proven to be helpful in tracking adverse events. More studies have been published using CTcue or a comparable tool to retrieve data from the EHR, including a validation study 27 , 30 , 31 . In the future, in case of a suspicion of the occurrence of a specific adverse event, a text mining tool can efficiently extract data from EHRs and can therefore quickly provide clarity on the relationship with the use of a particular drug.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated the incremental value of unstructured information over structured information in the prediction of a wide-range of topics. Combining unstructured and structured information improved the prediction of child abuse (Amrit et al, 2017), medication administration errors (Härkänen et al, 2020), suicide attempts (Adamou et al, 2018), use of health care services (Hatef et al, 2021), coronary artery disease (Jonnagaddala et al, 2015), and drug treatment outcomes (Laar et al, 2020). With regard to risk assessment of repeat victimization based on official police records, to the best of our knowledge, the incremental value of unstructured police information over structured police information is not yet investigated.…”
Section: Combining Structured and Unstructured Data For Risk Assessmentmentioning
confidence: 99%